Effect of Floor Cleaner Combination of Alcohol Ethoxylate-Sodium Lauryl Ether Sulfate and Combination of Carbol-Pine Oil on Ascaris lumbricoides Eggs - Simarmata, Vidi Posdo (Journal of Drug Delivery and Therapeutics, 2021)
Disinfectants are chemical agents used in disinfection in liquid form or solution form and are well-known as microbicidal, fungicidal, and virucidal but still unknown as parasiticidal, especially the effect to A. lumbricoides. In Indonesia, the prevalence of ascariasis is about 30,4% and still high. Ascariasis is caused by A. lumbricoides helminth that human swallows in egg form. Ascaris lumbricoides egg’s characteristics are hydrophobic and sticky, making it easy to stick on the floor, household, and skin. This research aims to find the difference between the combination of the effects of Alcohol Ethoxylate-Sodium Lauryl Ether Sulfate and the combination of Carbol-Pine Oil to A. lumbricoides eggshell and larva development as prevention and to break the life cycle chain of A. lumbricoides. The research results showed no effects from Alcohol Ethoxylate- Sodium Lauryl Ether Sulfate combination and Carbol-Pine Oil combination to A. lumbricoides eggshell and embryo development. Keywords: Disinfectants, ascariasis, concentration, eggshell, larva development.